(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
All aspects of our lives, including healthcare, are being reshaped by AI/ML (artificial intelligence/machine learning). Diabetic treatment might benefit greatly from the use of AI and ML, which could make it more effective and less time-consuming. In terms of data availability, the large number of diabetics in India brings a unique set of challenges, but it also gives an opportunity. With the use of electronic medical records, India may become a world leader in this field. The use of AI/ML might shed light on our issues and help us come up with solutions that are unique to each.